1980
DOI: 10.1017/s000335610002403x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body condition and time of mating on the reproductive performance of Masham ewes

Abstract: Masham ewes were mated at three stages of the breeding season, early (15 September to 20 October), mid (20 October to 24 November) and late (15 December to 19 January), at two different body condition scores, 4 and 2, for 3 successive years. The mean scores achieved for body condition 4 were 3-6, 3-7 and 3-9 for early, mid and late respectively and for body condition 2 were 2-4, 2-3 and 2-2. In the late lambing flock more ewes were marked by vasectomized rams and less ewes were barren than in the early and mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…In contrast, other studies report a positive effect of BCS on the number of lambs born in Scottish Black Face , Masham (Newton et al 1980) and various other breeds (Pollott & Kilkenny 1976).…”
Section: Number Of Lambs Born Per Ewementioning
confidence: 74%
See 3 more Smart Citations
“…In contrast, other studies report a positive effect of BCS on the number of lambs born in Scottish Black Face , Masham (Newton et al 1980) and various other breeds (Pollott & Kilkenny 1976).…”
Section: Number Of Lambs Born Per Ewementioning
confidence: 74%
“…The end point from a reproductive perspective for farmers is often the numbers of lambs weaned per ewe presented for breeding. Kleemann et al (2006) in an across-flock analysis with Merino ewes, Newton et al (1980) with Masham ewes, and Saul et al (2011) with Merino ewes all reported that BCS at breeding and/or mid-pregnancy was positively correlated with the number of lambs weaned per ewe exposed to the ram. Vatankhah et al (2012), with Lori-Bakhtiari ewes, reported that BCS at breeding had a positive effect on the number of lambs weaned per ewe, but only to a BCS of 3.0 before it plateaued.…”
Section: Effect Of Bcs On Ewe Reproductive Traitsmentioning
confidence: 94%
See 2 more Smart Citations
“…Çalışmada bulunan sonuçlar Gibb and Treacher (1982), Litherland et al, (1999), Thompson et al, (2011);Al-Sabbagh et al, (1995), Aliyari et al, (2012), Verbeek et al, (2012) ile benzer; Gibb and Treacher (1980), Kenyon et al, (2004), Kenyon et al, (2011), Mathias-Davis et al, (2013 ve Molina et al, (1991) Merinoslarda (McInnes and Smith 1966), Suffolk ırkında (Rozeboom et al, 2007) ve İvesi ırkında (Aliyari et al, 2012) yapılan çalışmalarda VKS ile fertilite ve litter size arasında ilişki olmadığı belirtilmiştir. Ancak bu durumun aksini iddia eden çalışmalarda mevcuttur Newton et al, 1980;Geisler and Fenlon 1979).…”
unclassified